Coverage and outcomes of antenatal tests for infections: a population based survey in the Province of Trento, Italy. (18th June 2019) - Dalmartello, Michela; Parazzini, Fabio; Pedron, Mariangela; Pertile, Riccardo; Collini, Lucia; La Vecchia, Carlo; Piffer, Silvano
Abstract: Background: Rubella, syphilis, toxoplasmosis, cytomegalovirus (CMV), hepatitis B (HBV) and C (HCV), HIV, and Group B Streptococcus (GBS) infections may have very severe outcomes during pregnancy, and for this reason, monitoring of infections in pregnant women is a requirement of prenatal assistance. Aims: To describe coverage and outcome of the screening for rubella, syphilis, toxoplasmosis, CMV, HBV, HCV, HIV, and Group B Streptococcus in pregnancy in the Autonomous Province of Trento, Northern Italy (538, 600 inhabitants). Methods: We analysed the coverage and outcome of the above-mentioned screenings among women who delivered in the hospitals of the Province of Trento between 2007 and 2014 ( N  = 38, 712). Screenings were grouped according to characteristics such as recommendation by national and local guidelines, scheduling of the tests, operating methods, and charge. We also estimated odds ratios (ORs) for missing screening for selected infections through multiple logistic regression. Results: Estimated uptake of antenatal screening was 99.7% for rubella, 99.3% for syphilis, 99.7% for toxoplasmosis, 98.1% for HIV infection, 99.0% for HBV, 98.9% for HCV, 94.0% for GBS infection, and 75.4% for CMV infection. The overall prevalence of immunity was 94.1% for rubella, 24.2% for toxoplasmosis, and 64.2% for CMV. The rate of seroconversion in pregnant women was 0.02% for rubella, 0.29% for toxoplasmosis, and 0.75% for CMV. The overall prevalence of infection was 0.94% for HBV, 0.53% for HCV, 22.3% for GBS, 0.29% for syphilis, and 0.13% for HIV. We found a significant positive association for all screening tests, between lack of testing and late first medical examination in pregnancy (ORs ranging from 1.20 to 1.66 for the first medical visit in the second trimester and ORs ranging from 1.60 to 5.88 for the first medical visit in third trimester, compared to early medical visit in the first trimester). Compared to Italian citizenship, foreign citizenship of the mother was also positively associated with absence of screening (ORs ranging from 1.30 to 1.53). A significant inverse association was observed for calendar year of delivery (ORs ranging from 0.71 to 0.97, for 1 year increment). Less educated mothers and pluriparae were also at higher risks of not being tested. Analysis of the association with mother age showed different heterogeneous effects. Conclusions: Our study indicates that the attention to screening and detecting infected cases is growing over the time. In addition, care delivered during pregnancy has a leading role in determining coverage of the examinations. Immigrant, pluriparous and less educated women need particular attention.